Cross-Border European Funding Opportunities - Miklós Lukovics; Imre Lengyel; Szabolcs Imreh; Bence Zuti (SZTE GTK, 2013)
Many Hungarian and foreign professionals are concerned with the issues regarding cross-border regions. Nowadays it is important to discuss this topic, as the European integration and globalisation extends the opportunities of cooperation between different states. As a matter of fact, the unification of Europe is considered one of the most significant processes in the 21st century. Even the new, even the older Member States have to face different challenges of cooperation. The establishment of connections between the nations is not only the interest of the European Union, but all states. In the European Union the transition between borders and the enhancement of cooperations are considered as primary questions. The cross-border cooperations can serve as a foundation to strengthen relations, so the actors can obtain funds even more easily together and they can use it more efficiently. The cross-border, transnational and interregional relations are considered as separate programmes in the regional policy of the European Union between the 2007-2013 programming period.
Additional information: Project ID: HURO/1001/148/2.3.1; HURO/1001/148/2.3.1
Keywords: I20; I23; I25; R10; R58; 330; Regional development; planning and policy; regional competitiveness